Weaponization of the Bible: Economic Exploitation and Cultural Alienation in Ngugi Wa Thiong’o And Ngugi Wa Mirii’s I Will Marry When I Want - Haruna, Abdullahi (International Journal of Language and Literary Studies, 2026)
This study examines the weaponization of the Bible in Ngugi wa Thiong’o and Ngugi wa Mirii’s I Will Marry When I Want through the lenses of Marxism and Fanonian theory. The research explores how the bible is used as a tool for economic exploitation and cultural alienation, perpetuating colonial and imperialist ideologies. By analyzing the play’s themes of neocolonialism, capitalism, and cultural identity, the study reveals the complex relationships among religion, power, and oppression. The study finds that the bible is used in I Will Marry When I Want as a tool for economic exploitation, perpetuating colonial and imperialist ideologies that maintain economic inequality through the dispossession of the proletariat. The play also depicts the bible as a symbol of cultural alienation, as characters struggle to reconcile their traditional values with the imposed Western values of colonialism.